Density functional theory and molecular dynamics simulation-based bioprospection of Agathosma betulina essential oil metabolites against protein tyrosine phosphatase 1B for interventive antidiabetic therapy - Oluwaseye Adedirin; Rukayat A. Abdulsalam; Khadeejah O. Nasir-Naeem; Ayenitaju A. Oke; Akolade O. Jubril; Saheed Sabiu (Heliyon)
Type II diabetes mellitus (T2DM) is characterized by elevated blood glucose due to impaired insulin secretion/sensitivity. While conventional antihyperglycemic medications like biguanides, sulfonylureas, and other agents are commonly used, their long-term use can have side effects, prompting research into natural alternatives. This study bioprospects the antidiabetic potential of metabolites in Agathosma betulina (Buchu) essential oil through computational analysis of their ability to inhibit protein tyrosine phosphatase 1B (PTP1B), a therapeutic diabetes target. Molecular dynamic simulation, supported by DFT analysis, revealed that compounds linalylanthranilate (−20.18 kcal/mol) and γ-diosphenol (−16.49 kcal/mol) found in the oil exhibited stronger PTP1B inhibition than ursolic acid (−15.98 kcal/mol). The compounds showed favorable drug-like properties complying with Lipinski's rules. This study provides the first evidence that these Buchu oil compounds could potentially serve as PTP1B inhibitors to enhance insulin receptor sensitivity, showing promise for T2DM treatment. Further validation through safety and clinical studies is recommended.